From Nucleic Acids Sequences to Molecular Medicine - Erdmann, Volker A.; Barciszewski, Jan.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
For this RNA Technologies volume a world-wide outstanding group of RNA specialists are contributing the most recent developments in this fast moving field of RNA molecular biology. The book features up-to-date information of our current knowledge on antisense, ribozyme, micro RNA, and DNAzyme strategies, as well as on other small RNAs from eukaryotes and prokaryotes, and the employment of chemical modifications to stabilize ribonucleic acids for their use in living cells. This volume is not only excellent reading for the expert in the field of RNA technologies, but also for those interested in entering this field as a chemist, molecular biologist or as a medical doctor interested in RNA therapeutics of the future.
From the contents -- Preface -- RNA (center of the) World. Non-coding RNAs: Identification of Cancer-Associated microRNAs. Antisense Oligonucleotides in the Treatment of Malignant Gliomas. The diverse active sites in splicing, debranching and microRNA processing around RNA phosphodiester bonds. Activation and Deactivation of Antisense Function with Light. Targeting catalytic RNAs into mitochondria for functional analyses and inverse genetics. Ribozymes as molecular biology reagents. Natural antisense transcripts mediate regulation of gene expression. Hammerhead ribozymes against virus and viroid RNAs. Chemical modification of short shRNAs. Antisense for treatment of cancer: the present and the future. Targeting non-coding RNAs for cancer therapy. Suppression of hepatitis C viral genome replication with Functional Antisense Oligonucleotides. Antisense-mediated reduction of eukaryotic non-coding RNAs.
Keywords: Medicine; Human genetics; Nucleic acids; Biomedicine; Molecular Medicine; Nucleic Acid Chemistry; Human Genetics